Chapter Signorie rurali, coscienza nobiliare e autorappresentazione - Bettotti, Marco (Reti Medievali E-Book, 2023)
The purpose of the essay is to show the choices made by noble Trentino families to propose an image of themselves, through different choices and thanks to different tools: building policy, iconographic, heraldic, funeral choices.